Rainout-sheltered lysimetric facility (PhysioTron) to generate precise phenotyping for drought tolerance traits under controlled conditions. - CGIAR Research Program on Wheat (2021)
The lysimeter at INRA-Morocco/ICARDA is fully functional, with HTP phenotyping equipment (Hiphen) to be soon installed.